Kegagalan Sistem Rekrutmen Partai Politik: Studi Kasus Biro PSI Jakarta Tahun 2020 - 2021 (Jurnal Nawala Politika, 2022)
Partai Solidaritas Indonesia is the fourth largest party in DKI Jakarta Province based on the results of the 2019 simultaneous general elections. PSI Jakarta established the Bureau on October 12, 2020. This study aims to analyze the location of the failure of the recruitment system and the location of the position of the Jakarta PSI Bureau using a qualitative research approach. Moving away from the recruitment model scheme of the political parties created by Pippa Norris as a scalpel to peeling more sharply into the findings focused on the passive performance of the bureau. Factors that influence the passive performance of the Bureau include: (1) The seriousness of the JAKARTA DPW PSI in directing the Bureau's management; (2) Lack of commitment for bureau administrators in carrying out performance; (3) There are no performance support facilities for the Bureau; (4) There is no old administrator of the Bureau as a mentor because this Bureau is indeed newly formed; (5) Recruitment by focusing on expertise. The recruitment selection stage of the Jakarta PSI Bureau in general, consists of administrative filing selection and interview selection. The bureau is a test material from Jakarta to attract people who have certain skills and can take the time.